Determinants of Economic Development in Nigeria: How Much Does Governance Matter? - Olabiyi, Kehinde Ajike; Olowookere, Johnson Kolawole (Universitas Negeri Semarang, 2021)
This study was carried out to determine the effects of governance on economic development in Nigeria. Annual time series data on Nigeria from 1996 to 2019 on GDP per capita, Control of corruption, Rule of Law, Voice and Accountability, Natural Resources, Investment, and Total Government Expenditure which were sourced from World Development Indicator database were used for the analysis. Auto Regressive Distributed Lag (ARDL) technique was employed in the study. The result indicated that the variables exhibited long run relationship and that all the explanatory variables are significant determinants of economic development (except Natural Resources) during the period of the study. The results suggested that a unit increase in the level of, control of corruption, investment, and total government expenditure dampens economic development by 26.3%, 8.08%, and 2.2% respectively in the long run, while a unit increase in voice and accountability, and income from natural resources enhance economic development in Nigeria by 57.5% and 3.7% respectively. The study therefore recommended the enhancement of good governance whereby citizens’ voice and choice prevail in government. Bureaucracy in government’s organization should also encourage accountability and transparency. Furthermore, an ideal policy environment that promotes domestic investment, and reduce cost of governance should be promulgated.